A method for enriching EPA and DHA in fish oil by low-temperature crystallization and high-activity fish oil
By modifying magnetic nano-ferrous oxide immobilizing lipase and synthesizing nano-hydroxyapatite and mixing urea on the surface of diatomaceous earth, the problems of poor lipase stability and low quality of urea-included fish oil were solved, and the efficient enrichment of EPA and DHA in fish oil and the preparation of highly active fish oil were achieved.
Patent Information
- Application Number
- CN202410987160.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-23
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-07-23
AI Technical Summary
Lipase has poor stability, complex separation after reaction, difficult recycling, and legal urea encapsulation, although the operation is simple, the quality of the enriched fish oil is not high.
By mixing collagen modifier with chitosan to coat the magnetic nano-iron oxide surface, the modified magnetic nano-iron oxide is mixed with dialdehyde starch and lipase, the lipase is immobilized to improve its stability and activity, and separated by an external magnetic field; at the same time, nano-hydroxyapatite is synthesized on the surface of diatomaceous earth and mixed with urea to form a stable crystal inclusion compound to improve the enrichment efficiency of EPA and DHA.
The stability and activity of lipase are improved, the separation and recovery process is simplified, and the content and purity of EPA and DHA in fish oil are significantly improved by low-temperature crystallization to obtain highly active fish oil.
Smart Images

Figure CN118652730B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fish oil processing and high-activity fish oil, in particular to a method for enriching fish oil EPA and DHA through low-temperature crystallization and high-activity fish oil. Background Art
[0002] Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in fish oil belong to the n-3 series of polyunsaturated fatty acids, which are a type of essential fatty acids that the human body cannot synthesize on its own. They have important health-care effects on the human body. The unsaturated fatty acids EPA and DHA promote lipid metabolism and bone metabolism, strengthen neurons, and improve fatty liver. They have important health-care effects on the human body. The methods for enriching polyunsaturated fatty acids in fish oil mainly include low-temperature solvent crystallization, urea inclusion complex, supercritical CO2 extraction, molecular distillation, enzyme concentration, etc.; to separate EPA and DHA, in order to increase the yield, multiple urea inclusion methods are generally used, which can form relatively stable crystalline inclusion complexes with saturated fatty acids or monounsaturated fatty acids in fish oil.
[0003] The use of lipase to extract and purify fish oil can increase the total amount of EPA and DHA in fish oil and achieve effective enrichment of EPA and DHA, but the stability of lipase is poor, and the separation of the enzyme after the reaction is complicated, requiring centrifugation and precipitation, resulting in difficult and incomplete recovery, and the recovered lipase is also difficult to reuse; the use of urea inclusion method to enrich EPA and DHA in fish oil not only has low raw material costs and simple operation, but the urea inclusion method is single and the quality of the enriched fish oil is not high. Summary of the invention
[0004] The purpose of the present invention is to provide a method for enriching EPA and DHA in fish oil through low-temperature crystallization and high-activity fish oil: a collagen modifier is mixed with chitosan and coated on the surface of magnetic nano iron oxide, thereby improving the stability of the magnetic nano iron oxide and avoiding the influence of poor colloidal stability of magnetite on the purity of fish oil; modified magnetic nano iron oxide, dialdehyde starch and lipase are mixed to enhance the fixation rate of lipase, thereby improving the stability and activity of lipase in the process of treating fish oil, and the immobilized enzyme is easily, quickly and efficiently separated from the fish oil through an external magnetic field, and the lipase still has high activity after recovery and is reusable; diatomaceous earth is mixed with calcium hydroxide and phosphoric acid, and after hydrothermal reaction, nano hydroxyapatite is synthesized on the surface of diatomaceous earth, and the synthesized nano The hydroxyl groups carried by rice hydroxyapatite can absorb metal ions in diatomaceous earth, preventing the metal ions in diatomaceous earth from falling into fish oil and affecting the quality of fish oil. It is then mixed with urea, and urea molecules are deposited on the surface of diatomaceous earth loaded with hydroxyapatite. During the low-temperature crystallization process, urea can form a relatively stable crystalline inclusion complex with saturated fatty acids or monounsaturated fatty acids and precipitate. The formed crystalline inclusion complex can precipitate together with the diatomaceous earth, thereby improving the removal rate. The loaded urea complexing agent is mixed with cellulose nanofibers and stirred for reaction. During the low-temperature crystallization process, the cellulose nanofibers and the loaded urea complexing agent form a hydrogen bond cross-linked network structure, which has more complexing sites for saturated fatty acids or monounsaturated fatty acids, thereby increasing the complexation removal of saturated fatty acids or monounsaturated fatty acids.
[0005] The technical problems to be solved by the present invention are as follows: poor stability of lipase, complex separation of lipase after reaction, difficulty in recovery, incomplete recovery, and difficulty in reusing the recovered lipase; the urea inclusion method is used to enrich EPA and DHA in fish oil, which not only has low raw material cost but also simple operation, but the urea inclusion method is single and the quality of the enriched fish oil is not high.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for enriching fish oil EPA and DHA by low temperature crystallization, comprising the following steps:
[0008] S1. The fish oil is mixed with lipase-loaded magnetic nanoparticles, deionized water is added, and an enzymatic hydrolysis reaction is performed. The mixture is treated with a magnetic separator to obtain pretreated fish oil.
[0009] Among them, the main component of fish oil is triglyceride. The lipase in the lipase-loaded magnetic nanoparticles can hydrolyze the triglyceride containing saturated fatty acids at the 1 and 3 positions in the fish oil into diglycerides and monoglycerides, and the partial glyceride lipase in the lipase-loaded magnetic nanoparticles can convert diglycerides and monoglycerides into fatty acids, which is beneficial to the subsequent low-temperature crystallization to remove fatty acids, thereby increasing the content of EPA and DHA in fish oil.
[0010] Furthermore, the fish oil is selected from any one of tuna oil, salmon oil and anchovy oil.
[0011] Furthermore, the mass ratio of fish oil, lipase-loaded magnetic nanoparticles, and deionized water is (90-110):(8-10):(8-12).
[0012] Furthermore, the enzymolysis temperature is 30-50°C, and the enzymolysis time is 2-4h.
[0013] More preferably, the enzymolysis temperature is 40° C. and the enzymolysis time is 3 h.
[0014] S2. Add the pretreated fish oil and the composite inclusion agent into ethanol, stir for inclusion, cool for crystallization, remove the crystals by filtration, and then recover the ethanol by rotary evaporator to obtain enriched fish oil EPA and DHA.
[0015] Furthermore, the dosage ratio of the pretreated fish oil, the composite inclusion agent, and the ethanol is (70-90) g: (90-110) g: (220-260) mL.
[0016] Furthermore, the inclusion temperature is 70-80°C, and the inclusion time is 0.5-2h.
[0017] More preferably, the inclusion temperature is 75° C. and the inclusion time is 1 h.
[0018] Furthermore, the crystallization temperature is 20-30°C.
[0019] Furthermore, the lipase-loaded magnetic nanoparticles are prepared by mixing modified magnetic nano-iron oxide, dialdehyde starch and lipase.
[0020] Furthermore, the lipase is prepared by mixing immobilized Sn-1,3 specific lipase and partial glyceride lipase in a mass ratio of (3.5-4.5) g:(4-6) g.
[0021] Furthermore, the dialdehyde starch has an aldehyde content of 25.1-39.4% and a molecular weight of 15.36-17.23 kDa.
[0022] Furthermore, the lipase-loaded magnetic nanoparticles are prepared by the following steps:
[0023] Dialdehyde starch and modified magnetic nano-iron oxide were added to deionized water, ultrasonically treated for 15 minutes to make them uniformly dispersed, sodium hydroxide was added, and the mixture was stirred at 40°C and 150 rpm for 4 hours, filtered, washed with deionized water three times, and dried in an oven at 40°C for 10 minutes to obtain a solid. The solid and lipase were added to a phosphate buffer with a concentration of 0.1 M, stirred at 150 rpm for 30 minutes, the supernatant was separated by magnetic separation, and washed with phosphate buffer three times, washed with deionized water three times, and dried in an oven at 30°C for 10 minutes to obtain magnetic nanoparticles loaded with lipase.
[0024] Among them, sodium hydroxide is used as a catalyst to make the aldehyde group at one end of dialdehyde starch combine with the amino and hydroxyl groups on the surface of modified magnetic nano-iron oxide through chemical bonds, so that the dialdehyde starch is partially grafted on the surface of modified magnetic nano-iron oxide. Dialdehyde starch is used as a cross-linking agent, and the aldehyde group it contains can react with a large number of protein amino groups in lipase, thereby fixing the lipase on the surface of modified magnetic nano-iron oxide.
[0025] Furthermore, in phosphate buffer, the modified magnetic nano-iron oxide without dialdehyde starch grafted thereon has oxygen-containing functional groups on its surface that react with the carboxyl group in the lipase, so that the lipase is fixed on the surface of the modified magnetic nano-iron oxide through covalent bonds, thereby enhancing the fixation rate of the lipase. The surface of the modified magnetic nano-iron oxide also contains an ionic structure, which enhances the fixation of the lipase, thereby improving the stability and activity of the lipase in the process of processing fish oil.
[0026] Furthermore, the dosage ratio of dialdehyde starch, modified magnetic nano iron oxide, deionized water and sodium hydroxide is (2-3) g: (0.1-0.3) g: (45-55) mL: (0.1-0.3) g.
[0027] Furthermore, the dosage ratio of solid, lipase and phosphate buffer is (0.1-0.3) g: (8-12) g: (35-45) mL.
[0028] Furthermore, the phosphate buffer has a concentration of 0.1 M and a pH of 7.
[0029] Further, dialdehyde starch is specifically prepared by the following steps:
[0030] Add corn starch to deionized water, stir evenly, add a 2.3 mol / L sodium periodate aqueous solution, stir, add 85% by mass phosphoric acid to adjust the pH to 3.5, stir at 30°C for 4 hours, filter the solution, wash the product 3 times with deionized water, and freeze-dry at -10°C to obtain dialdehyde starch.
[0031] Among them, sodium periodate, as an oxidant, can oxidize the hydroxyl groups in starch into aldehyde groups. As a cross-linking agent for lipase, its molecular chain is large and can isolate heat sources, thereby improving the thermal stability of lipase, reducing the effect of heat on the enzyme, and preventing the enzyme from being inactivated by heat.
[0032] Furthermore, the usage ratio of corn starch, deionized water, sodium periodate aqueous solution, and phosphoric acid is (3-5) g:(18-22) mL:(2.5-2.9) mL:(3-5) mL.
[0033] Furthermore, the modified magnetic nano-iron oxide is prepared by mixing a collagen modifier with chitosan and coating the mixture on the surface of the magnetic nano-iron oxide.
[0034] Furthermore, the collagen modifier is prepared by mixing squaric acid and collagen in a mass ratio of (0.2-0.3):(0.1-0.2).
[0035] Furthermore, the particle size of the magnetic nano-iron oxide is 30-100 nm.
[0036] Furthermore, the modified magnetic nano iron oxide is prepared by the following steps:
[0037] The collagen modifier and chitosan were added to an acetic acid aqueous solution with a mass dispersion of 1%, stirred evenly, and magnetic nano-iron oxide was added. The mixture was stirred and reacted at 30°C for 2 hours. The mixture was filtered, washed with deionized water for 3 times, and dried in an oven at 50°C for 24 hours to obtain modified magnetic nano-iron oxide.
[0038] Among them, the carbonyl and hydroxyl groups contained in the squaric acid in the collagen modifier can undergo cross-linking reactions with the primary amino groups of chitosan, and the oxygen-containing functional groups and ester groups can be chemically bonded to the hydroxyl groups on the surface of the magnetic nano-iron oxide, so that the chitosan is coated on the surface of the magnetic nano-iron oxide, thereby improving the stability of the magnetic nano-iron oxide and avoiding the poor colloidal stability of magnetite affecting the purity of the fish oil.
[0039] Furthermore, squaric acid forms ionic compounds with collagen, which can increase the activity of lipase, thereby enhancing the hydrolysis of triglycerides in fish oil by lipase and increasing the total amount of EPA and DHA in fish oil.
[0040] Furthermore, the dosage ratio of collagen modifier, chitosan, acetic acid aqueous solution, and magnetic nano-iron oxide is (0.3-0.5) g: (0.1-0.3) g: (35-45) mL: (0.2-0.4) g.
[0041] Furthermore, collagen is prepared by the following steps:
[0042] Sheep tendon was selected and washed with deionized water, then immersed in 50 mL of 0.1 M acetic acid aqueous solution at 4°C for 4 days, and then centrifuged at 3000 r / min for 20 min. The supernatant was collected and placed in a dialysis bag. The dialysis bag was placed in 100 mL of deionized water and dialyzed for 2 days to obtain a transparent protein solution. The protein solution was freeze-dried at -20°C for 48 hours to obtain collagen.
[0043] Furthermore, the usage ratio of sheep tendon and acetic acid aqueous solution is (8-12) g:(45-55) mL.
[0044] Furthermore, the composite inclusion agent is prepared by mixing the loaded urea complexing agent with the cellulose nanofibers and stirring the mixture for reaction.
[0045] Furthermore, the cellulose nanofibers have a diameter of 50-100 nm and a length of 1.5-3 μm.
[0046] Further, the composite inclusion agent is specifically prepared by the following steps:
[0047] The loaded urea complexing agent and cellulose nanofibers were added to deionized water, stirred evenly, reacted at 40°C for 3 hours, cooled to room temperature, washed with deionized water for 3 times, and dried in an oven at 60°C for 10 minutes to obtain a composite inclusion agent.
[0048] Among them, the amino groups contained on the surface of the loaded urea complexing agent are combined with the hydroxyl groups on the surface of the cellulose nanofibers through hydrogen bonds, so that the loaded urea complexing agent is dispersed in the cellulose system. During the low-temperature crystallization process, urea is dissolved in the organic solvent ethanol. Under the action of the cellulose nanofibers and the hydroxyapatite in the loaded urea complexing agent, the urea molecules are dispersed in the cellulose system to form a hydrogen-bonded cross-linked network structure with more complexing sites for saturated fatty acids or monounsaturated fatty acids, thereby increasing the complexation and removal of saturated fatty acids or monounsaturated fatty acids, and achieving effective enrichment of EPA and DHA.
[0049] Furthermore, the dosage ratio of the loaded urea complexing agent, cellulose nanofibers, and deionized water is (2-3) g: (5.4-5.8) g: (15-25) mL.
[0050] Furthermore, the loaded urea complexing agent is prepared by mixing diatomaceous earth with calcium hydroxide and phosphoric acid, subjecting the mixture to a hydrothermal reaction, and then mixing the mixture with urea.
[0051] Furthermore, the hydrothermal reaction temperature is 50-70°C, and the hydrothermal reaction time is 1-3h.
[0052] Further, the loaded urea complexing agent is specifically prepared by the following steps:
[0053] A 1.2 mol / L calcium hydroxide aqueous solution and a 0.6 mol / L phosphoric acid aqueous solution were mixed, stirred evenly, diatomaceous earth was added, mixed at 400 rpm for 30 min, heated to 60° C., stirred for reaction for 2 h, cooled to room temperature, filtered, washed with deionized water 3 times, dried in an oven at 65° C. for 10 min, placed in ethanol, added with urea, stirred evenly, stirred at 85° C. until the organic solvent evaporated, cooled to room temperature, and obtained a loaded urea complexing agent.
[0054] Among them, calcium ions in calcium hydroxide can be adsorbed on the surface of diatomaceous earth through electrostatic action, and calcium ions combine with phosphate to form calcium phosphate complex. After hydrothermal treatment, the calcium phosphate complex crystallizes to form nano-hydroxyapatite, thereby realizing the synthesis of nano-hydroxyapatite on the surface of diatomaceous earth. The hydroxyl groups carried by the synthesized nano-hydroxyapatite can adsorb metal ions in diatomaceous earth, thereby preventing the metal ions in diatomaceous earth from falling into the fish oil and affecting the quality of the fish oil.
[0055] Furthermore, the hydroxyl structure contained in the diatomite loaded with hydroxyapatite can be electrostatically bonded with the amino group in the urea molecule, so that the urea molecule is deposited on the surface of the diatomite loaded with hydroxyapatite.
[0056] Furthermore, the mass ratio of calcium hydroxide aqueous solution, phosphoric acid aqueous solution, diatomaceous earth and urea is (3-4):(2-3):(2.5-2.7):(8-12).
[0057] Furthermore, compared with the prior art, the present invention has the following beneficial effects:
[0058] (1) In the technical scheme of the present invention, the squaric acid in the collagen modifier reacts with chitosan, and the oxygen-containing functional groups and ester groups contained therein can be combined with the magnetic nano-iron oxide through chemical bonds, so that the chitosan is coated on the surface of the magnetic nano-iron oxide, thereby improving the stability of the magnetic nano-iron oxide and avoiding the poor colloidal stability of magnetite affecting the purity of the fish oil. The squaric acid in the collagen modifier forms a cross-linked ionic compound with the collagen, and the ionic chemical can increase the activity of lipase, thereby enhancing the hydrolysis of triglycerides in the fish oil by lipase, increasing the total amount of EPA and DHA in the fish oil, and achieving effective enrichment of EPA and DHA.
[0059] (2) In the technical solution of the present invention, the lipase includes Sn-1,3 specific lipase and partial glycerol lipase. Sn-1,3 specific lipase can hydrolyze triglycerides containing saturated fatty acids at positions 1,3 in fish oil into diglycerides and monoglycerides, and partial glycerol lipase can convert diglycerides and monoglycerides into fatty acids, which is beneficial for the subsequent low-temperature crystallization to remove fatty acids, thereby increasing the content of EPA and DHA in fish oil. The lipase is fixed on the surface of modified magnetic nano-iron oxide, and the lipase can also be fixed on the surface of modified magnetic nano-iron oxide by dialdehyde starch, which enhances the fixation rate of the lipase, thereby improving the stability and activity of the lipase in the process of treating fish oil. In addition, the dialdehyde starch has a large molecular chain and can isolate heat sources, thereby improving the thermal stability of the lipase, reducing the effect of heat on the enzyme, and preventing the enzyme from being inactivated by heat. Magnetic nanoparticles serve as carriers of lipase. After lipase catalyzes the hydrolysis of triglycerides in fish oil, the immobilized enzyme can be easily, quickly and efficiently separated from the fish oil through an external magnetic field. After recovery, the lipase still has high activity and is reusable.
[0060] (3) In the technical scheme of the present invention, nano-hydroxyapatite is synthesized on the surface of diatomite. The hydroxyl groups carried by the synthesized nano-hydroxyapatite can adsorb metal ions in the diatomite, thereby preventing the metal ions in the diatomite from falling into the fish oil and affecting the quality of the fish oil. The hydroxyl structure contained in the diatomite loaded with hydroxyapatite can electrostatically bond with the amino groups in the urea molecules, so that the urea molecules are deposited on the surface of the diatomite loaded with hydroxyapatite. The diatomite loaded with hydroxyapatite serves as a carrier of urea molecules and has a large specific surface area, thereby increasing the contact area between urea and saturated fatty acids in fish oil. In addition, during the low-temperature crystallization process, urea can form a relatively stable crystal inclusion complex with saturated fatty acids or monounsaturated fatty acids and precipitate. The formed crystal inclusion complex can precipitate together with the diatomite, thereby increasing the removal rate and thus increasing the purity of DHA and EPA in fish oil. In addition, diatomite has a huge surface area. As a crystallization aid, diatomite can promote the crystallization of saturated fatty acids in fish oil and improve the efficiency of enriching DHA and EPA in fish oil.
[0061] (4) In the technical solution of the present invention, the loaded urea complexing agent is dispersed in the cellulose system. During the low-temperature crystallization process, urea is dissolved in the organic solvent ethanol. Under the action of cellulose nanofibers and hydroxyapatite in the loaded urea complexing agent, urea molecules are dispersed in the cellulose system to form a hydrogen-bonded cross-linked network structure with more complexing sites for saturated fatty acids or monounsaturated fatty acids, thereby increasing the complexing removal of saturated fatty acids or monounsaturated fatty acids and achieving effective enrichment of EPA and DHA.
[0062] (5) In the technical solution of the present invention, EPA and DHA are extracted from fish oil by a composite method of enzymatic hydrolysis and urea low-temperature crystallization, which has a high extraction efficiency, thereby obtaining fish oil with high content of EPA and DHA, and the enriched fish oil EPA and DHA have high natural activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0064] Figure 1 The following is a diagram showing the test results. DETAILED DESCRIPTION
[0065] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0066] The raw materials used in the embodiments of the present invention are as follows: tuna oil, salmon oil, anchovy oil (purchased from Wilmar Oil Chemical (Shanghai) Co., Ltd.); immobilized Sn-1,3-specific lipase (purchased from Novozymes, Denmark); partial glyceride lipase (model Lipase AOL); corn starch (AR, amylose content of 26%, molecular weight of 168.29 kDa); sodium periodate (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.); sheep tendon (purchased from Hebei Kaiyang Leather Co., Ltd.); acetic acid (analytical grade, purchased from Sinopharm Group Reagent Co., Ltd.); squaric acid (model 2892-51-5, purity 98%); chitosan (70.21 kDa, purity 86.1%).
[0067] Dialdehyde starch is specifically prepared by the following steps:
[0068] Add 4 g corn starch to 20 mL deionized water, stir evenly, add 2.7 mL of 2.3 mol / L sodium periodate aqueous solution, stir, add 5 mL of 85% phosphoric acid to adjust the pH to 3.5, stir at 30 ° C for 4 hours, filter the solution, wash the product 3 times with deionized water, and freeze-dry at -10 ° C to obtain dialdehyde starch.
[0069] Collagen is specifically prepared by the following steps:
[0070] 10 g of sheep tendon was selected, washed with deionized water, immersed in 50 mL of 0.1 M acetic acid aqueous solution, soaked at 4°C for 4 days, and then centrifuged at 3000 r / min for 20 min. The supernatant was collected and placed in a dialysis bag. The dialysis bag was placed in 100 mL of deionized water and dialyzed for 2 days to obtain a transparent protein solution. The protein solution was freeze-dried at -20°C for 48 hours to obtain collagen. Example 1
[0071] The lipase-loaded magnetic nanoparticles are prepared by the following steps:
[0072] A1. Mix 0.25g of squaric acid and 0.15g of collagen to obtain a collagen modifier, add 0.4g of collagen modifier and 0.2g of chitosan into 40mL of 1% acetic acid aqueous solution, stir evenly, add 0.3g of magnetic nano-iron oxide, stir and react at 30°C for 2h, filter, wash with deionized water 3 times, and dry in an oven at 50°C for 24h to obtain modified magnetic nano-iron oxide.
[0073] A2. Add 2.5g of dialdehyde starch and 0.2g of modified magnetic nano-iron oxide to 50mL of deionized water, ultrasonically treat for 15min to make it uniformly dispersed, add 0.2g of sodium hydroxide, stir at 40℃ and 150rpm for 4h, filter, wash with deionized water 3 times, dry in a 40℃ oven for 10min to obtain a solid, add 0.2g of the solid and 10g of lipase to 40mL of 0.1M phosphate buffer, stir at 150rpm for 30min, separate the supernatant by magnetic separation, wash with phosphate buffer 3 times, wash with deionized water 3 times, and dry in a 30℃ oven for 10min to obtain lipase-loaded magnetic nanoparticles. The lipase is a mixture of immobilized Sn-1,3-specific lipase and partial glyceride lipase in a mass ratio of (3.5-4.5)g:(4-6)g. Comparative Example 1
[0074] The difference between this comparative example and Example 1 is that the modified magnetic nano-iron oxide is replaced by magnetic nano-iron oxide, and the remaining steps and raw materials are the same as Example 1.
[0075] 2.5g of dialdehyde starch and 0.2g of magnetic nano-iron oxide were added to 50mL of deionized water, ultrasonically treated for 15min to make it uniformly dispersed, 0.2g of sodium hydroxide was added, stirred at 40℃ and 150rpm for 4h, filtered, washed with deionized water 3 times, and dried in an oven at 40℃ for 10min to obtain a solid, 0.2g of the solid and 10g of lipase were added to 40mL of 0.1M phosphate buffer, stirred at 150rpm for 30min, the supernatant was separated by magnetic separation, washed with phosphate buffer 3 times, washed with deionized water 3 times, and dried in an oven at 30℃ for 10min to obtain lipase-loaded magnetic nanoparticles. Among them, the lipase is a mixture of immobilized Sn-1,3-specific lipase and partial glyceride lipase in a mass ratio of (3.5-4.5)g:(4-6)g. Comparative Example 2
[0076] The difference between this comparative example and Example 1 is that no dialdehyde starch is added, and the remaining steps and raw materials are the same as Example 1.
[0077] A1. Mix 0.25g of squaric acid and 0.15g of collagen to obtain a collagen modifier, add 0.4g of collagen modifier and 0.2g of chitosan into 40mL of 1% acetic acid aqueous solution, stir evenly, add 0.3g of magnetic nano-iron oxide, stir and react at 30°C for 2h, filter, wash with deionized water 3 times, and dry in an oven at 50°C for 24h to obtain modified magnetic nano-iron oxide.
[0078] A2. Add 0.2g of modified magnetic nano-iron oxide and 10g of lipase to 40mL of 0.1M phosphate buffer, stir at 150rpm for 30min, separate the supernatant by magnetic separation, wash with phosphate buffer 3 times, wash with deionized water 3 times, and dry in an oven at 30℃ for 10min to obtain lipase-loaded magnetic nanoparticles. The lipase is a mixture of immobilized Sn-1,3-specific lipase and partial glyceride lipase in a mass ratio of (3.5-4.5)g:(4-6)g. Example 2
[0079] The composite inclusion agent is specifically prepared by the following steps:
[0080] B1. Mix 3.6 g of 1.2 mol / L calcium hydroxide aqueous solution and 2.5 g of 0.6 mol / L phosphoric acid aqueous solution, stir evenly, add 2.6 g of diatomaceous earth, mix at 400 rpm for 30 min, heat to 60°C, stir to react for 2 h, cool to room temperature, filter, wash 3 times with deionized water, dry in an oven at 65°C for 10 min, place in 30 mL of ethanol, add 10 g of urea, stir evenly, stir at 85°C until the organic solvent evaporates, cool to room temperature, and obtain a loaded urea complexing agent.
[0081] B2. Add 2.5 g of loaded urea complexing agent and 5.6 g of cellulose nanofibers into 20 mL of deionized water, stir evenly, react at 40 °C for 3 h, cool to room temperature, wash three times with deionized water, and dry in an oven at 60 °C for 10 min to obtain a composite inclusion agent. Comparative Example 3
[0082] The difference between this comparative example and Example 2 is that the loaded urea complexing agent is replaced by urea and diatomaceous earth, and the remaining steps are synchronized with Example 2.
[0083] Add 2.1 g urea, 2.2 g diatomaceous earth and 5.6 g cellulose nanofibers into 20 mL deionized water, stir evenly, react at 40° C. for 3 h, cool to room temperature, wash three times with deionized water, and dry in an oven at 60° C. for 10 min to obtain a composite inclusion agent. Comparative Example 4
[0084] The difference between this comparative example and Example 2 is that no cellulose nanofibers are added, and the remaining steps are synchronized with Example 2.
[0085] Mix 3.6 g of 1.2 mol / L calcium hydroxide aqueous solution and 2.5 g of 0.6 mol / L phosphoric acid aqueous solution, stir evenly, add 2.6 g of diatomaceous earth, mix at 400 rpm for 30 min, heat to 60° C., stir to react for 2 h, cool to room temperature, filter, wash 3 times with deionized water, dry in an oven at 65° C. for 10 min, place in 30 mL of ethanol, add 10 g of urea, stir evenly, stir at 85° C. until the organic solvent evaporates, cool to room temperature, and obtain a loaded urea complexing agent. Example 3
[0086] A method for enriching fish oil EPA and DHA by low temperature crystallization, comprising the following steps:
[0087] S1. 90 g of tuna oil was mixed with 8 g of lipase-loaded magnetic nanoparticles, 8 g of deionized water was added, and the mixture was hydrolyzed at 30° C. for 2 h. After being treated with a magnetic separator, pretreated fish oil was obtained.
[0088] S2. Add 70g of pretreated fish oil and 90g of the composite inclusion agent into 220mL of ethanol, stir and include at 75°C for 1h, then reduce the temperature to 25°C for crystallization, remove the crystals and the composite inclusion agent by filtration, and then recover the ethanol by rotary evaporator to obtain enriched fish oil EPA and DHA. Example 4
[0089] A method for enriching fish oil EPA and DHA by low temperature crystallization, comprising the following steps:
[0090] S1. Mix 100 g salmon oil with 9 g lipase-loaded magnetic nanoparticles, add 10 g deionized water, hydrolyze at 30° C. for 2 h, and process with a magnetic separator to obtain pretreated fish oil.
[0091] S2. Add 80g of pretreated fish oil and 100g of the composite inclusion agent into 240mL of ethanol, stir and include at 75°C for 1h, then reduce the temperature to 25°C for crystallization, remove the crystals and the composite inclusion agent by filtration, and recover the ethanol by rotary evaporator to obtain enriched fish oil EPA and DHA. Example 5
[0092] A method for enriching fish oil EPA and DHA by low temperature crystallization, comprising the following steps:
[0093] S1. 110 g of anchovy oil was mixed with 10 g of lipase-loaded magnetic nanoparticles, 12 g of deionized water was added, and the mixture was hydrolyzed at 30° C. for 2 h. The mixture was treated with a magnetic separator to obtain pretreated fish oil.
[0094] S2. Add 90g of pretreated fish oil and 110g of the composite inclusion agent into 260mL of ethanol, stir and include at 75°C for 1h, then reduce the temperature to 25°C for crystallization, remove the crystals and the composite inclusion agent by filtration, and recover the ethanol by rotary evaporator to obtain enriched fish oil EPA and DHA. Comparative Example 5
[0095] The difference between this comparative example and Example 4 is that the lipase-loaded magnetic nanoparticles are replaced by the material prepared in Comparative Example 1, and the remaining steps and raw materials are the same as those in Example 4. Comparative Example 6
[0096] The difference between this comparative example and Example 4 is that the lipase-loaded magnetic nanoparticles are replaced by the material prepared in Comparative Example 2, and the remaining steps and raw materials are the same as those in Example 4. Comparative Example 7
[0097] The difference between this comparative example and Example 4 is that the composite inclusion agent is replaced by the substance prepared in Comparative Example 3, and the remaining steps and raw materials are the same as those in Example 4. Comparative Example 8
[0098] The difference between this comparative example and Example 4 is that the composite inclusion agent is replaced by the substance prepared in Comparative Example 4, and the remaining steps and raw materials are the same as those in Example 4.
[0099] The enriched fish oil EPA and DHA prepared in Examples 3-5 and Comparative Examples 5-8 are now tested;
[0100] The salmon oil selected by the present invention has a saturated fatty acid content of 44.2% and a total content of EPA and DHA of 31.5%.
[0101] The content and activity of EPA and DHA in the enriched fish oil EPA and DHA prepared above were tested with reference to GB 5009.168-2016 standard, and the content of EPA and DHA in the product was determined by gas chromatography using the area normalization method. Chromatographic conditions: chromatographic column 123-7032DB-WAX (30mx0.25mm); split ratio 60:1; vaporization temperature 240°C; detector temperature 280°C; programmed temperature rise; carrier gas pressure 1mL / min; hydrogen flow rate 30mL / min; air flow rate 300mL / min; injection volume 0.2μL. The test results are as follows Figure 1 shown.
[0102] Depend on Figure 1The data show that in Comparative Example 5, the modified magnetic nano-iron oxide is replaced with the loaded lipase magnetic nano-particles prepared by the magnetic nano-iron oxide, and used to treat fish oil, the recovery rate and the total amount of EPA and DHA enriched in the fish oil decrease. This may be because chitosan is coated on the surface of the magnetic nano-iron oxide, which improves the stability of the magnetic nano-iron oxide and avoids the poor colloidal stability of magnetite affecting the purity of the fish oil. The collagen modifier squaric acid forms a cross-linked ionic compound with collagen, and the ionic compound can increase the activity of lipase, thereby enhancing the hydrolysis of triglycerides in the fish oil by lipase, and increasing the total amount of EPA and DHA in the fish oil; Comparative Example 6 is a loaded lipase magnetic nano-particle prepared without adding dialdehyde starch, and used to treat fish oil. The recovery rate and the total amount of EPA and DHA enriched in the fish oil decrease. This may be because the dialdehyde starch can also fix the lipase on the surface of the modified magnetic nano-iron oxide, thereby enhancing the fixation rate of the lipase, thereby improving the stability and activity of the lipase in the process of treating fish oil; In comparative example 7, the urea-loaded complexing agent is replaced with a composite inclusion agent prepared by urea and diatomaceous earth for treating fish oil, and the recovery rate and total amount of EPA and DHA enriched in fish oil decrease. This may be because nano-hydroxyapatite is synthesized on the surface of diatomaceous earth to prevent metal ions in diatomaceous earth from falling into the fish oil and affecting the quality of fish oil; and urea molecules are deposited on the surface of diatomaceous earth loaded with hydroxyapatite. During the low-temperature crystallization process, urea can form a relatively stable crystalline inclusion complex with saturated fatty acids or monounsaturated fatty acids and precipitate, and the formed crystalline inclusion complex can precipitate together with diatomaceous earth, thereby improving the removal rate; in comparative example 8, the composite inclusion agent prepared without adding cellulose nanofibers is used to treat fish oil, and the recovery rate and total amount of EPA and DHA enriched in fish oil decrease. This may be because during the low-temperature crystallization process, under the action of cellulose nanofibers, a hydrogen-bonded cross-linked network structure is formed, which has more complexation sites for saturated fatty acids or monounsaturated fatty acids, thereby increasing the complexation removal of saturated fatty acids or monounsaturated fatty acids.
[0103] Depend on Figure 1Data shows that the method for enriching fish oil EPA and DHA by low temperature crystallization in Example 3-5 has a high recovery rate and high content of enriched fish oil EPA and DHA, and the prepared enriched fish oil EPA and DHA have high natural activity. Fish oil is mixed with magnetic nanoparticles loaded with lipase, deionized water is added, and after enzymatic hydrolysis, it is treated by a magnetic separator to obtain pretreated fish oil; the pretreated fish oil and the composite inclusion agent are added to ethanol, stirred for inclusion, cooled and crystallized, the crystals are removed by filtration, and the ethanol is recovered by a rotary evaporator to obtain enriched fish oil EPA and DHA to meet the test performance requirements, while the enriched fish oil EPA and DHA prepared in Comparative Examples 5-8 do not meet the performance requirements, indicating that the method for enriching fish oil EPA and DHA by low temperature crystallization of the present invention has a high recovery rate and high content of enriched fish oil EPA and DHA, and the prepared enriched fish oil EPA and DHA have high natural activity.
[0104] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0105] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for enriching fish oil EPA and DHA by low temperature crystallization, characterized in that: The following steps are involved: S1. mixing fish oil with lipase-loaded magnetic nanoparticles, adding deionized water, performing enzymatic hydrolysis, and then treating with a magnetic separator to obtain pretreated fish oil; The lipase-loaded magnetic nanoparticles are prepared by mixing modified magnetic nano-iron oxide, dialdehyde starch and lipase; The modified magnetic nano-iron oxide is prepared by mixing a collagen modifier with chitosan and coating the mixture on the surface of the magnetic nano-iron oxide. The collagen modifier is prepared by mixing squaric acid and collagen in a mass ratio of (0.2-0.3):(0.1-0.2); S2. The pretreated fish oil and the composite inclusion agent are added to ethanol, stirred for inclusion, cooled and crystallized, the crystals are removed by filtration, and the ethanol is recovered by a rotary evaporator to obtain enriched fish oil EPA and DHA; The composite inclusion agent is prepared by mixing a loaded urea complexing agent with cellulose nanofibers and stirring the mixture for reaction; The loaded urea complexing agent is prepared by mixing diatomaceous earth, calcium hydroxide and phosphoric acid, subjecting the mixture to a hydrothermal reaction, and then mixing the mixture with urea.
2. A method for enriching fish oil EPA and DHA by low temperature crystallization according to claim 1, characterized in that: The lipase is prepared by mixing immobilized Sn-1,3 specific lipase and partial glyceride lipase in a mass ratio of (3.5-4.5) g:(4-6) g.
3. The method for enriching fish oil EPA and DHA by low temperature crystallization according to claim 1, characterized in that: The dialdehyde starch is specifically prepared by the following steps: Add corn starch to deionized water, stir evenly, add a 2.3 mol / L sodium periodate aqueous solution, stir, add 85% by mass phosphoric acid to adjust the pH to 3.5, stir at 30°C for 4 hours, filter the solution, wash the product 3 times with deionized water, and freeze-dry at -10°C to obtain dialdehyde starch.
4. The method for enriching fish oil EPA and DHA by low temperature crystallization according to claim 3, characterized in that: The usage ratio of corn starch, deionized water, sodium periodate aqueous solution and phosphoric acid is (3-5) g: (18-22) mL: (2.5-2.9) mL: (3-5) mL.
5. The method for enriching fish oil EPA and DHA by low temperature crystallization according to claim 1, characterized in that: The hydrothermal reaction temperature is 50-70° C., and the hydrothermal reaction time is 1-3 hours; the cellulose nanofiber has a diameter of 50-100 nm and a length of 1.5-3 μm.
6. The method for enriching fish oil EPA and DHA by low temperature crystallization according to claim 1, characterized in that: In the step S1, the enzymolysis temperature is 30-50°C, and the enzymolysis time is 2-4h; in the step S2, the inclusion temperature is 70-80°C, the inclusion time is 0.5-2h, and the crystallization temperature is 20-30°C.
7. The method for enriching fish oil EPA and DHA by low temperature crystallization according to claim 1, characterized in that: In step S1, the mass ratio of fish oil, lipase-loaded magnetic nanoparticles, and deionized water is (90-110):(8-10):(8-12).
8. The method for enriching fish oil EPA and DHA by low temperature crystallization according to claim 1, characterized in that: In the step S2, the ratio of the pretreated fish oil, the composite inclusion agent, and the ethanol is (70-90) g: (90-110) g: (220-260) mL.
Citation Information
Patent Citations
Method for catalytically synthesizing phytosterol ester compound by using magnetic immobilized lipase
CN112029756A
Nanometer hydroxyapatite / natural polymer composite material, preparation method and use thereof
WO2011035573A1